PENGARUH PELAKSANAAN PENAGIHAN PAJAK DAN SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA BATAM - ITA MUSTIKA ITA MUSTIKA (Jurnal Kajian Akuntansi dan Auditing, 2021)
The purpose of this study is to determine the effect of the variable (X1) is the implementation of tax collection and variable (X2) that is Self Assessment System to (Y) taxpayer compliance. The object of this research is KPP Pratama Batam, which is specially in KPP Pratama area of ​​North Batam. In this research, sampling technique is done by Random Sampling method, using Solvin formula which produce 100 respondent / sample. Data analysis technique using SPSS (Statistical Package for the Social Science) version 22. The result of this research is the implementation of tax collection (X1) and self assessment system (X2) has a significant effect on taxpayer compliance (Y)